Influence of a synthetic ureido nucleating agent on crystallization behavior and mechanical properties of polyamide 6. Issue 9 (3rd February 2015) - Ouyang, Chunfa; Xue, Weili; Zhang, Duoyou; Gao, Qun; Li, Xiangyong; Zheng, Kangsheng
<x xml:space="preserve">Abstract</x> A synthetic ureido mixture prepared from the reaction of 4, 4′‐diphenylmethane disocynanate (MDI) and cyclohexylamine without using any harmful organic solvents, has been used as a nucleating agent (PNA) for polyamide 6 (PA6). The effect of PNA on the crystallization and mechanical properties of PA6 has been studied by means of differential scanning calorimetry (DSC), polarized optical microscopy (POM), tensile test, melt flow index (MFI), and X‐ray diffraction (XRD). The results show that PNA is an effective nucleation agent for PA6. PNA affects the nucleation mechanism of PA6, and substantially accelerates the crystallization rate of PA6 and gives rise to smaller crystal size. In comparison with PA6, the crystallization temperature (Tc) of PA6/PNA (100/0.5) increases 21.3°C and the degree of sub‐cooling (ΔTc) decreases 23.7°C. Furthermore, because of the heterogeneous nucleation induced by PNA, the spherulites of PA6 become even and tiny based on POM observation. Polymorph transform has been obtained from XRD analysis. The virgin PA6 is free of γ‐phase crystals, presented as α‐phase crystals in this study, but γ‐phase crystal appears after the introduction of PNA. The mechanical and thermal properties of PA6 are obviously improved by the addition of PNA. POLYM. ENG. SCI., 55:2011–2017, 2015. © 2015 Society of Plastics Engineers